Partnership Agreement: Study of Liquid Organic Fertilizer Processing on CV. Guna Daya Persada - Kelik Wardiono; Faiq Muhammad Rafi (Universitas Muhammadiyah Surakarta, 2023)
The contract contains rights and settles the obligations of the parties. One side performs its obligations and has the right to get its rights, and vice versa. However, sometimes there are parties who do not carry out their achievements based on the agreement and make other parties feel disadvantaged. In civil law, a wish that is flawed or unfulfilled is called default or breach of contract. default is a term which means broken promise, found in book III BW. The purpose of the research is to describe the legal contract construction of CV. Guna Daya Persada and describes the legal protection of the parties in the agreement between CV. Guna Daya Persada with Mr. Ismail. The research method used is the normative approach method, namely the approach with the main source being a provision of the law and secondary data, namely the partnership cooperation agreement between CV. Guna Daya Persada with Mr. Ismail. The legal construction of the partnership cooperation agreement between CV. Guna Daya Persada with Mr. Ismail is a sui generis agreement or a mixed agreement between a work contract agreement and a sale and purchase agreement because the main rights and obligations in the agreement are in accordance with Article 1601 letter (b), Articles 1606, 1608 and 1457 of the Civil Code and there is legal protection in in terms of the obligation of the contractor to provide liquid organic fertilizer seeds to the contractor and pay for the work or processing of the contractor and the contractor's obligation to work on or process liquid organic fertilizer seeds that have been provided by the contractor to the fullest and best and hand over the processed products to the buying party. This is in line with Article 1601 letter (b), Article 1606 and Article 1457 of the Civil Code.